Tingkat Pendidikan sebagai Patokan Belis Perempuan Sumba - Anisa Ndula Awang; Lis Susilawati; Harry Surahman (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
The belis tradition is no longer something new for the people of Eastern Indonesian, especially in the East Nusa Tenggara region. This tradition has noble values and is also a form of respect for women. The issue of the belis tradition process in the level of education as benchmark for belis Sumba women is very interesting to study scientifically,especially why the people in Watumbaka Village still maintain education as a benchmark for belis. The aim of this research is to describe the impact of education on the traditional belis process for every Summbanese woman. The method used in the resarch is qualitative with a descriptive approach. Data collection methods use interviews and documentation. Then the data was analyzed through three stages, namely data reduction, data presentation and drawing conclusions so that a systematic series was arranged. The research result showed that the belis tradition of the Sumba people had experienced a shift where belis was determined based on a woman’s education level and no longer according to the mpther’s belis strata. The belis tradition is no longer maintained traditionally but rather follows the times and educational developments.